Pengaruh E-Commerce Terhadap Proses Jual Beli Masyarakat Saat Ini Khususnya Pada Penggunaan Market Online Bukalapak - Yasin, Muhammad; Saseno, Guntur; Dewi, Ratih Novinditya; Setyowati, Nur Dewi (Universitas Merdeka Madiun, 2018)
E-commerce as a media to buy and sell online begins to develop and is widely discussed because it is recognized to provide various benefits such as ease of transaction, so that transactions can be done anytime and anywhere. Now, many large-scale business and micro, small and medium-sized businesses are starting to implement e-commerce. And the fact that not a few business people have benefited from the success of e-commerce, but also not a few business people who experience failure even some do not know whether e-commerce has achieved success or not. One market place that is often used by people for sale / purchase transactions is BUKALAPAK, is one of the leading markets (online marketplace) in Indonesia which is owned and operated by PT. Bukalapak. With the aim that various conveniences in making transactions and offering discounts can attract public interest to change the style of selling / buying goods manually (physically) to selling / buying goods based on online products.